Spektroskopische Untersuchung von Ammonium-oxodiperoxoamminovanadat(V) - Baran, Enrique José (1977)
The infrared and electronic spectra of NH₄[VO(O₂)₂NH₃] are recorded and interpreted. The results are discussed and some comparisons with related species are made.